Preparedness of Senior High School Students and Modular Distance Learning Education in the New Normal: A Framework for a Plan of Action - Guzman, Jaypee; Guitering-Mansibang, Cayselyn (International Journal of Arts, Sciences and Education, 2022)
The quantitative approach, particularly the descriptive-comparative research design, was utilized to assess the extent of the preparedness of the senior high school students for distance modular learning education in the new normal in terms of their study skills, motivation, and time management. There were 120 participants in the study who were composed of students from the Academic Track and Technical Vocational Livelihood Track. The questionnaire served as the principal instrument of the analysis. The data analysis was carried out using ANOVA, z-test, frequency, percentage, and weighted mean. The study results revealed that the disadvantages of modular distance learning education prevail more than its advantages. Thus, one’s preparedness is influential and significant to the success of distance learning education. Furthermore, there is no significant difference in the students’ preparedness to modular learning when grouped according to their age. The same result also showed that there is no significant difference in the students’ preparedness to modular learning when grouped according to sex, while there is a significant difference in the extent of students’ preparedness to modular learning when grouped according to their senior high school track. The researchers suggest the crafting of the plan of action should be worked out together with the School Planning Team to give proper resources and allocation in the Annual Implementation Plan and School Improvement Plan of the school, which are also part of the School-Based Management, whose priority is to improve the school and students’ performances.